Mediation: religious and cultural disputes - Ali Mohamed, Ashgar Ali; Yaakob, Adnan; Ramalingam, Chitra Latha (The Malaysian Current Law Journal Sdn Bhd, 2020)
Malaysia is a multi-ethnic and multi-religious country with Muslim, Hindus, Buddhists and Christians living together harmoniously. Its citizens are not only given freedom to practice their religious beliefs and cultures but are also thought to be tolerant and respectful to other religious beliefs and cultural practices.1 Undoubtedly, these values are vital for harmony to prevail in society and the country. Harmonious ties among the different races and cultures2 are necessary for the progress and betterment of the country. To touch on the sensitive aspects of another’s religious beliefs and cultural practices is in fact treading on dangerous grounds